2023
DOI: 10.17555/jvc.2023.40.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Red Ginseng Marc and Steamed Extraction Powder Enhance Proliferation and Inflammatory Cytokine Modulation in Canine PBMCs Stimulated by IL-2

Abstract: The growing market for companion animals, combined with their increasing lifespan, has generated an increased interest in companion animal immunity enhancers. Ginsenoside, a saponin component of ginseng and an essential ingredient of red ginseng marc (produced during red ginseng production), is effective in improving immunity. In this experiment, a powder mixture of red ginseng marc and steamed red ginseng extract powder (RGME) was orally administered to dogs for eight weeks. Subsequently, blood samples were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It was recently reported that red ginseng dregs and steamed red ginseng can enhance the immunity of dogs by increasing the level of interferon-γ released by peripheral blood mononuclear cells in dogs stimulated by IL-2. The dogs were orally treated with red ginseng residue and steamed red ginseng powder for eight weeks (An et al, 2023). Famous traditional Chinese Medicine (TCM) Dendrobium officinale Kimura et Migo (D. officinale) mixed with American ginseng increases the number of shortchain fatty acids producing bacteria to prevent gut dysbiosis.…”
Section: Use Of Ginseng In Companion Animalsmentioning
confidence: 99%
“…It was recently reported that red ginseng dregs and steamed red ginseng can enhance the immunity of dogs by increasing the level of interferon-γ released by peripheral blood mononuclear cells in dogs stimulated by IL-2. The dogs were orally treated with red ginseng residue and steamed red ginseng powder for eight weeks (An et al, 2023). Famous traditional Chinese Medicine (TCM) Dendrobium officinale Kimura et Migo (D. officinale) mixed with American ginseng increases the number of shortchain fatty acids producing bacteria to prevent gut dysbiosis.…”
Section: Use Of Ginseng In Companion Animalsmentioning
confidence: 99%